Behavioral aspect of people in the Patan museum - Adhikari, Richa; Thapa, Aabha (Journal of Innovations in Engineering Education, 2026)
This research examines visitor behavior in a heritage museum, focusing on how spatial layout and exhibit design affect engagement and interaction. It employs both observational methods and structured analysis to understand how factors such as age, exhibit design, and spatial arrangement influence the visitor experience. The findings reveal that different age groups exhibit distinct behavioral patterns. Older visitors tend to prefer interactive activities that allow active participation rather than passive observation. Younger visitors favor open and spacious layouts, as crowded environments create discomfort. Exhibits that are closely linked to historical or cultural narratives significantly increase visitor engagement. The study further highlights the importance of spatial organization, demonstrating that clear sightlines and unobstructed circulation improve interaction. These findings offer evidence based guidelines for improving museum design and enhancing the overall visitor experience.